Implementation of the Make A Match Learning Model in Improving Student Learning Outcomes in Islamic Education Learning at SD Negeri 104313 Sarang Puah - Irwanto, Andri; Handayani, Irma; Sari, Nilam (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2023)
This study aims to Improve Student Learning Outcomes in Islamic Education Using the Make A Match Learning Model. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained using test and observation techniques. Tests are used to improve student learning outcomes in developing a character of mutual respect and observation is used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that learning using the Make A Match Learning Model can improve learning outcomes. This can be seen from the increase in the percentage of completeness of improving student learning outcomes in each cycle with details of the pre-cycle 45.64%, the first cycle 76.57% and in the second cycle increased to 87.57%. Thus, learning using the Make A Match Learning Model can be used as an alternative to improve student learning outcomes.